WEB-BASED MOBILE SERVICE HANDLING APPLICATION DESIGN - Teni Agustina; Dewi Aryanti; Mochamad Nandi Susila; Mulyadi Mulyadi; Andronias Siregar; Hardiyan Hardiyan (INFOKUM, 2022)
The use of internet technology has developed with the presence of web-based applications as a solution to a problem in an organization. CV. Dayla Cell is a business actor selling services for accessories and handling mobile phone service and as an object of research. The problem that exists in the object of research is the management of service data, which still uses paper records physically and is not yet supported by database data storage. The purpose of this study is to design and build a web-based application that can support the effectiveness and productivity of research object service handling activities, with the benefit of research being able to provide convenience and speed in searching for the required data because the data is stored properly in a database. This study uses the SDLC (Software Development Life Cycle) software development method with the stages of the waterfall method. The results of the study are that the applications built are able to properly support operational activities, especially mobile phone service on the object of research